2002
DOI: 10.1101/gad.988502
|View full text |Cite
|
Sign up to set email alerts
|

The barrier function of an insulator couples high histone acetylation levels with specific protection of promoter DNA from methylation

Abstract: Stably integrated transgenes flanked by the chicken ␤-globin HS4 insulator are protected against chromosomal position effects and gradual extinction of expression during long-term propagation in culture. To investigate the mechanism of action of this insulator, we used bisulfite genomic sequencing to examine the methylation of individual CpG sites within insulated transgenes, and compared this with patterns of histone acetylation. Surprisingly, although the histones of the entire insulated transgene are highly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
162
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 175 publications
(172 citation statements)
references
References 43 publications
9
162
1
Order By: Relevance
“…We infer that the insulator-induced changes in CpG methylation at this site do not determine expression of the transgene, but the insulator-induced changes in expression determine CpG methylation of the promoter site. This inference is compatible with a model proposed by Felsenfeld and his associates (12,13) based on their analysis of chromatin modifications associated with a transgene flanked with two copies of cHS4. Our experiments show that two flanking copies of cHS4 are more potent than a single flanking copy in protecting the transgene from repression and its promoter from CpG methylation.…”
Section: Dna Methylation Of the Transgene On Xa But Not XI Is Affectesupporting
confidence: 71%
See 1 more Smart Citation
“…We infer that the insulator-induced changes in CpG methylation at this site do not determine expression of the transgene, but the insulator-induced changes in expression determine CpG methylation of the promoter site. This inference is compatible with a model proposed by Felsenfeld and his associates (12,13) based on their analysis of chromatin modifications associated with a transgene flanked with two copies of cHS4. Our experiments show that two flanking copies of cHS4 are more potent than a single flanking copy in protecting the transgene from repression and its promoter from CpG methylation.…”
Section: Dna Methylation Of the Transgene On Xa But Not XI Is Affectesupporting
confidence: 71%
“…Flanking copies of cHS4 without the CTCF binding site can still protect randomly integrated transgenes from position effects. In a position effect assay the cHS4 insulator itself and transgenes flanked with it are associated with acetylated histones, histone H3 methylated at lysine 4, and reduced CpG methylation relative to the methylation of uninsulated transgenes (11)(12)(13).…”
mentioning
confidence: 99%
“…2,10,[15][16][17][18][19] Previous reports have shown that HS4 insulator protects transgenes from position effect variegation when introduced into MoMLV-based retroviral vectors. 20,21 Since the HS4 fragment is active in restricted cell types, 21 a quest for alternative insulators is necessary to propagate the use of the insulator in various cell types and tissues.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown in turn in the fungus Neurospora that the ability to methylate histone Lys 9 is essential for DNA methylation 28 , suggesting that local methylation at Lys 9 may provide a signal for methylation of the underlying DNA. Furthermore, in a different reaction pathway, maintenance of histone acetylation at promoters can lead to inhibition of DNA methylation 29 .…”
Section: Epigenetic Inheritancementioning
confidence: 99%